LAYANAN KONSELING PERORANGAN DENGAN TEKNIK KURSI KOSONG UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI INTERPERSONAL - Muth Muthohharoh; Yeni Karneli (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
This research begins from the background regarding each individual's interpersonal communication skills that need to be improved in this globalization era. As an empty chair technical intervention in individual counseling services provided to have interpersonal communication skills, one of those skills is maintaining good communication in the daily environment, especially with parents. This study uses a quantitative method using a survey research design that aims to determine the effectiveness of individual counseling services with empty chair techniques to improve interpersonal communication skills. The purpose of this study is to find a picture of the effectiveness of individual counseling services with empty chair techniques to improve interpersonal communication skills and to find out individual counseling services with effective empty chair techniques to improve interpersonal communication skills. Data processing was performed by comparing the scores of pretest and posttest results on a client (S) aged 20 years. Analysis of the research data used is based on client respondents (S) on the DASS instrument before and after the implementation of individual counseling services with the empty chair technique. Thus it can be concluded that individual counseling services with the empty chair technique are effective for improving interpersonal communication skills.